Trade union membership and works councils in West Germany - Laszlo Goerke; Markus Pannenberg (Institute for the Study of Labor (IZA), 2007)
The fraction of works councillors belonging to a trade union in Germany is much higher than union density among employees. If works councils represent the face of unions, union membership of employees should be related positively to the existence of works councils and their proximity to unions. Using data from the German Socio-Economic-Panel SOEP we find that (a) works councillors exhibit a higher probability of being a union member, (b) the mere existence of a works council within an establishment has no impact on union membership and (c) a 10 % decrease in the average share of unionised works councillors coincides with a 10 % fall in the probability of being a union member. Hence, the decline in the unionisation of works councillors and the fall in union density in West Germany are closely linked.
urn:nbn:de:101:1-20080416288
Keywords: 330; Gewerkschaft; Mitgliedschaft; Betriebsrat; Alte Bundesländer